The Influence of Service Quality on Word of Mouth Through Patient Satisfaction and Trust as Mediating Variables at Balad Medical Center Clinic, Pariaman - Nela Vernanda; Yunia Wardi (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the influence of service quality on WOM through satisfaction and trust at Balad Medical Center Clinic. The research method used was descriptive quantitative, with a sample of 200 patients. The analysis used PLS-SEM analysis with Smart-PLS 4.0. The results showed service quality, patient satisfaction, and trust significantly influenced WOM. Service quality significantly influenced patient satisfaction and trust. Patient satisfaction and trust mediated the relationship between service quality and WOM. Balad Clinic needs to improve service quality to increase patient satisfaction and trust, thus creating positive WOM. Therefore, the study results are expected to enrich the literature and provide practical recommendations for clinic in improving service quality, satisfaction, trust, and WOM.